Theoretical Model of Engagement in the Context of Brand Communities - Flávia D\u2019albergaria Freitas; Victor Manoel Cunha de Almeida (BBR: Brazilian Business Review)
This essay proposes to refine the concept of consumer engagement in the context of brand communities. A comprehensive review of studies addressing the phenomenon of brand community was made. This paper follows the tradition of Marketing Research and Consumer Behavior, more specifically the perspective of cognitive psychology. The main theoretical foundation of the study is the Social Identity Theory (SIT), also incorporating relevant contributions from the perspective of Consumer Culture Theory (CCT). Therefore, this study contributes to the progress of research on the phenomenon of engagement in brand communities, proposing a theoretical model that relates engagement with its antecedents factors and reflective dimensions.